Indigenous Inclusion in Global Trade: New Zealand’s CPTPP Strategy for Māori (2019–2023) (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
This study aims to analyze how New Zealand achieves Māori inclusion in trade through the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP). New Zealand's policy is crucial for addressing three main challenges: the need for adaptation and a deep understanding of cultural, political, and trade practices aligned with the CPTPP. The methods used in this study include document analysis, policy analysis, and a literature review to understand the relationship between New Zealand and the Māori in cooperating under a free trade agreement. The research findings indicate that during the 2019–2023 period, New Zealand undertook several policy initiatives to achieve inclusive trade for Māori through the CPTPP. These policies include the establishment of the official board TFAAB, which functions to provide recommendations and critiques regarding decisions and policies made by the Crown related to inclusive trade in the CPTPP. New Zealand also established institutions and support communities that specifically act as Māori representatives in addressing provisions to be agreed upon in the CPTPP, such as Te Taumata, Ngā Toki Whakarururanga, FOMA, and the National Iwi Chairs Forum. During this period, New Zealand also offered solutions to address claims raised by the Māori, such as the revision of the Plant Variety Act and matters related to digital trade.